2018
DOI: 10.46792/fuoyejet.v3i1.138
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitive Action of Water Extract of Spondias Mombin on Corrosion of Low Carbon Steel in 0.5 M Sulphuric Acid

Abstract: Corrosion inhibition of water extract of Spondias mombin on low carbon steel in 0.5 M sulphuric acid was investigated in this paper. Fresh leaves, fruits and bark of this plant, washed properly, ground separately using small amount of distilled water to extract the juice at a ratio of 500 ml (distilled water) to 1 kilogram of plant were used for this experiment. Corrosion inhibitors of 0.4 g/ml, 1 g/ml and 2 g/ml were made from the filterate. Low carbon steel coupons suspended with twine inside 250 ml containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Table 3 shows that both extracts addition lowers the i_corr values, which implies that the extracts lowers the corrosion rate of the steel. However, it was observed that the ethanol extract causes the greater reduction in i_corr which confirms that the ethanol extract performs better than the water extract (Obi-Egbedi et al, 2014;Sidikat et al, 2018;Al-Otaibi et al, 2014).…”
Section: ) Potentiodynamic Polarization (Pdp)mentioning
confidence: 87%
See 2 more Smart Citations
“…Table 3 shows that both extracts addition lowers the i_corr values, which implies that the extracts lowers the corrosion rate of the steel. However, it was observed that the ethanol extract causes the greater reduction in i_corr which confirms that the ethanol extract performs better than the water extract (Obi-Egbedi et al, 2014;Sidikat et al, 2018;Al-Otaibi et al, 2014).…”
Section: ) Potentiodynamic Polarization (Pdp)mentioning
confidence: 87%
“…From Figure 4, it can be seen that the adsorption of the Spondias mombin extract followed the Langmuir and Freundlich isotherms. This indicates that the extract components adsorbed as single layer on very roughened steel surface during the corrosion (Sidikat et al, 2018;Obi-Egbedi et al, 2012). This mode of adsorption could easily detach.…”
Section: Adsorption Isotherm Analysismentioning
confidence: 94%
See 1 more Smart Citation